Affect and the Rise of the Self-Regulating Market - Gammon, Earl (Millennium: Journal of International Studies, 2008)
This article outlines a post-rationalist approach to international political economy that factors in the role of affect in social causation. There are key historical junctures where social transformations cannot be neatly explained by instrumental logics, such as the profit motive or the pursuit of increasing productive efficiency. Affect, in the form of anxiety and aggression, overdetermines social behaviour in ways that belie conventional notions of rationality, premised on a clear ordering of needs or preferences by social actors. This analysis specifically reassesses the role of affect in the rise of market civilisation in Britain in the early part of the nineteenth century. It critiques Karl Polanyi's account, which privileges technology and pecuniary greed as the expedients of the institution of the self-regulating market. As an alternative, this article explains the rise of the self-regulating market as a retributive mechanism, whereby the market became conceived as a means of punishing and disciplining social behaviour in the early Victorian period. The market, I argue, was an aggressive response to anxiety that plagued Victorian society regarding social order, an anxiety precipitated by the waning belief in a natural moral economy guided by the hand of Providence.
Keywords: Great Britain; affect; critique; international political economy; post-rationalist IPE; self-regulating market; social causation